BMT Development Strategies In The Era Of Covid-19 Pandemic With A SWOT Analysis Approach - Usep Deden Suherman; Dedi Suyandi (JPS (Jurnal Perbankan Syariah), 2023)
This research aims to analyze the strengths, weaknesses, opportunities, and threats to the positioning and development strategy of Baitul Maal Wa Tamwil (BMT) in West Java in the Era of the Covid-19 Pandemic. The descriptive qualitative research method was used. The study was conducted at 6 BMTs in the West Java region Technique of data analysis used is SWOT analysis. The results of the calculation of the SWOT matrix produce several alternative strategies, namely utilizing government support for Islamic banking by increasing the types of Sharia products, approaching potential investors even though capital is limited considering the public interest in the Islamic economy is very high, making regional regulations on sharia economics, establishing cooperation and partnerships with other financial institutions to obtain capital, capacity building of human resources, training, and development activities through partnerships with other banks that apply sharia principles. The implications of the results of this research are as input material for the development of new policies, strategies, and efforts to develop BMT both in the pandemic era and after the Covid-19 pandemic and to develop theories for alternative strategies in developing BMT in the Covid-19 pandemic era.